RESCHEDULING SYSTEM IN UMRAH TRAVEL ACCORDING TO SHARIA ECONOMIC LAW: A STUDY OF TRAVEL COMPANIES IN BANDA ACEH INDONESIA - Fadhila Maisura; Achyar, Gamal (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
This article aims to examine the departure rescheduling system on Umrah travel in Banda Aceh in accordance with the provisions in the ijārah 'ala al-'amāl contract. This research uses a normative sociological approach with descriptive qualitative methods to analyze the implementation of Umrah based on the provisions of Islamic law. Data is obtained through interviews, documentation, and observation. Rescheduling is the process of readjusting the umrah travel schedule which is often done for various reasons, such as personal constraints, illness, or administrative problems. The results showed that the application of the ijārah 'ala al-'amāl contract in umrah travel allows the umrah traveler to provide optimal service and fulfill the rights of jama'ah, while effectively managing the rescheduling process to minimize the negative impact of departure delays. This study examines the application of the umrah departure rescheduling system, especially in terms of the relationship between umrah travel and prospective pilgrims at PT Katana Travel & Tour and Pt Dar Tauhid Haramain in Banda Aceh. It is known that the two trips often dispatch Umrah and receive rescheduling requests. This study aims to understand the rescheduling mechanism as well as the challenges faced by the travel party and the congregation and its suitability with the principle of Ijârah 'ala al-'amâl contract in fiqh muamalah.